Invasive Bromus tectorum alters natural selection in arid systems. (20th October 2017) - Leger, Elizabeth A.; Goergen, Erin M.
Summary: While much research has documented the impact of invaders on native communities and ecosystem services, there has been less work quantifying how invasion affects the genetic composition of native populations. That is, when invaders dominate a community, can they shift selection regimes and impact the evolutionary trajectory of native populations? The invasion of the annual grass Bromus tectorum in the Intermountain West provides an opportunity to quantify the effects of invasion on natural selection in wild populations. The shift from a perennial‐dominated native community to one dominated by a highly competitive annual species alters the timing and intensity of competitive pressure, which has the potential to strongly shift selection regimes for native plants. To quantify traits under selection in contrasting environments, we planted seeds of two native perennial grasses, Elymus multisetus and Poa secunda, into three invaded, invaded but weeded and relatively uninvaded sagebrush systems. We quantified phenotypic traits of seedlings from separate maternal plants, describing differences in phenotypes among individuals. We then asked which traits were associated with survival and plant size in adjacent invaded and uninvaded sagebrush systems, following individual seed performance for 3 years. We found evidence for divergent selection between invaded and uninvaded sagebrush systems, with contrasting phenotypic traits associated with greater survival or plant size in these different growing conditions at all three field sites. For example, at one field site, P. secunda families with higher root tip production were more likely to survive in invaded and weeded environments, but this was not the case in uninvaded environments. Similarly, for E. multisetus, root mass fraction, seed mass and allocation to coarse or fine roots affected survival and plant size, again with contrasting relationships across invaded, weeded or uninvaded environments. Synthesis . Impacts of invasive species extend beyond ecosystem and community composition changes and can affect the evolutionary trajectory of native populations. By quantifying natural selection in invaded landscapes, we identified phenotypic traits that are potentially adaptive in these invaded systems. Importantly, these traits differed from traits associated with success in uninvaded communities. This insight into adaptive, contemporary evolution in native species can guide restoration and conservation efforts. Abstract : Invasive Bromus tectorum has drastically changed conditions in sagebrush steppe communities in the Intermountain West. Using precision seeding methods and reciprocal transplant studies, we examined changes in natural selection associated with plant invasion. Focusing on seedlings of two native perennial grasses, we found that contrasting phenotypes were associated with survival and plant size in adjacent invaded/uninvaded communities. Our results demonstrate that the impacts of invasive species extend beyond ecosystem and community composition changes, and that invasive species can also affect the evolutionary trajectory of native populations.